Deconstructing Hindu Practices: A Study Based on Deepa Mehta’s Trilogy - Anutharsi, G.; Poongulaly, S. (University of Jaffna, 2025)
Films illuminate the complexities of tradition, gender, culture and identity in the society in which we live. Directors play a pivotal role in shaping and presenting reality on screen. Over time, the depiction of Hindu practices, rituals, and local customs has evolved, reflecting changes in societal attitudes, cultural values and religious practices. According to that, this study examines the portrayal of Hindu religious practices, symbols, and beliefs in Deepa Mehta's trilogy Water (2005), Earth (1998) and Fire (1996) as her work represents the socio-religious structures rooted in Hindu practices and their intersections with gender, societal norms and power dynamics. The primary objective of this study is to examine how Mehta depicts the Hindu practices of Indian society through her settings, characters, themes, and storytelling in her films. The secondary objectives include exploring the depiction of challenges in Indian society’s reality and how she uses symbols to explore the depiction of Hindu practices. This study employs a textual analysis of films’ key sequences, including the plot, characters, visual elements, and audio, explicitly focusing on conversations between the main characters. Feminist film theory and Auteur theory were used for the study. In the film Water, Mehta challenges the difficulties of widows how the religious is manipulating them to exploit throughout their livelihood. In the film Fire, the director critically argues the impositions of patriarchal society how emphasised within religious and societal customs. Meanwhile, Earth delves into the communal tensions of the 1947 Partition, illustrating how religious identities are weaponised to fuel political and societal violence. The study concludes that by deconstructing the traditionalised interpretations of Hinduism, Mehta's films provoke a re-evaluation of the intersection between religion and social justice. This research highlights her cinematic narratives how used as tools for questioning oppressive traditions, expressing the marginalised difficulties and advocating for inclusivity and reform in contemporary Indian society. Deepa Mehta questions the cultural projections of binary oppositions, such as oppressor and oppressed power structures that shape Indian society.
Keywords: Hindu practices; Deconstruction; Deepa Mehta; Trilogy; Textual analysis; Auteur theory